Challenges of targeting BRAF V600E mutations in adult primary brain tumor patients: a report of two cases - Matthew Smith-Cohn; Christian Davidson; Howard Colman; Adam L Cohen (CNS Oncology, 2019)
Aim: Therapeutic targeting of BRAF alterations in primary brain tumor patients has demonstrated clinical activity in case reports and early trials; however, there is limited high-level evidence of the efficacy. Patients & results: Targeting BRAF V600E mutations with concurrent dabrafenib and trametinib in anaplastic pleomorphic xanthoastrocytoma resulted in a transient radiographic and clinical response and no therapeutic benefit in a patient with an epithelioid glioblastoma. Conclusion: BRAF/MEK inhibition did not produce a durable treatment effect in glioblastoma or pleomorphic xanthoastrocytoma with BRAF V600E alterations. Heterogenicity of related cases in the literature makes an evaluation of efficacy BRAF targeting therapies in gliomas difficult and requires additional investigation.